Exploration of the Use of Management Accounting Systems in Improving the Financial Performance of Small And Medium Enterprises in Lhoksukon District - Dora, Moulinda; Damanik, Janner (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to explore the application of Management Accounting System (MAS) in improving the financial performance of Small and Medium Enterprises (SMEs) in Lhoksukon District, North Aceh. MAS is a system designed to assist in more structured financial management, including planning, controlling, and decision-making based on accounting data. Although MAS has been proven to improve financial transparency and operational efficiency, its application in Lhoksukon is still very limited. This study uses a qualitative approach with in-depth interviews and direct observation of 100 MSMEs’ engaged in the trade, livestock, and small industry sectors, as well as village government officials. The results of the study show the application of the Management Accounting System (MAS) in MSMEs’ in Lhoksukon District. Of the 100 MSME actors interviewed, only 31 have adopted SAM, with the trade and small industry sectors showing a higher adoption rate than the agriculture and livestock sectors. Although MAS has been proven to improve the efficiency of financial management, many MSME actors still use manual recording due to limited knowledge, implementation costs, and time for training. These findings indicate the need for further support to educate MSMEs’ about the benefits of MAS and provide broader access to training.